Parâmetros hemetológicos da tilápia-do-Nilo: efeito da dieta suplementada com levedura e zinco e do estímulo pelo frio - Signor, Altevir; Pezzato, Luiz Edivaldo [UNESP]; Falcon, Dario Rocha; Guimarães, Igo Gomes; Barros, Margarida Maria [UNESP] (FapUNIFESP (SciELO), 2010)
Hematological parameters of Nile tilapia fed diets supplemented with increasing levels of autolised yeast and zinc, before and after cold stress, were analyzed. The diets were formulated to contain 32.0% DP and 3,240 kcal/kg DE with increasing levels of autolised yeast (%) and zinc (mg/kg), as: 0.0:0.0; 0.0:79.5; 2.0:0.0; 0.795:79.5; 2.0:200; 4.0:400; 6.0:600; 12.0:1.200; 14.0:1400 . In phase I, 135 fingerlings were distributed into 27 50l-aquaria and fed ad libitum four times a day during 128 days (26ºC). After that, phase II began and nine fish from each treatment were transferred to 27 40l-aquaria (three/aquarium) and submitted to cold temperature (13.0ºC) during seven days. Before and after cold stress, the following parameters were evaluated: erythrocytes number, hematocrit, hemoglobin, corpuscular volume, mean corpuscular volume, total plasmatic protein, total leucocytes, lymphocytes, neutrophils and monocytes percentage. The number of erythrocytes was significantly influenced by the addition of autolised yeast and zinc to the diets. After cold stress, fish fed diets supplemented with 0.795:79.50 (Lev:Zn) and 14:1400 (Lev:Zn) presented impaired erythrocyte synthesis. Absence of test nutrients determined significant decrease in hematocrit, total leukocyte and total plasmatic protein. Cold stress determines leukopenia, lymphopenia, neutrophylia and monopenia.

Objetivou-se avaliar os parâmetros hematológicos da tilápiado-nilo alimentada com dietas suplementadas com níveis de levedura autolisada e zinco, anterior e posterior ao estímulo pelo frio. As dietas foram formuladas para conter 32,0% PD e 3.240 kcal ED/kg com adição de levedura autolisada (%) e zinco (mg/kg): 0,0:0,0; 0,0:79,5; 2,0:0,0; 0,795:79,5; 2,0:200; 4,0:400; 6,0:600; 12,0:1200 e 14,0:1400. Na fase I, 135 alevinos foram distribuídos em 27 aquários de 50L e alimentados quatro vezes/dia por 128 dias (26ºC). Posteriormente, iniciou-se a fase II. Nove peixes/tratamento foram transferidos para 27 aquários de 40L (três/aquário) e submetidos à baixa temperatura (13,0ºC) por sete dias. Antes e após o estímulo pelo frio avaliaramse: o número de eritrócitos, a porcentagem de hematócrito, a taxa de hemoglobina, o volume corpuscular médio, a concentração de hemoglobina corpuscular média, a proteína plasmática e leucócitos totais, a porcentagem de linfócitos, neutrófilos e monócitos. O número de eritrócitos foi influenciado (p<0,05) pela adição de levedura autolisada e zinco nas dietas. Após o estímulo pelo frio o maior prejuízo na eritropoiese ocorreu nos peixes que receberam dietas 0,795:79,50 (Lev:Zn) e 14:1.400 (Lev:Zn). A ausência dos nutrientes-testes determinou queda significativa no hematócrito, leucócitos e proteína plasmática total. O estresse pelo frio determina leucopenia, linfopenia, neutrofilia e monopenia.
Hematological parameters of Nile tilapia: effect of diet and cold stress
Keywords: Healthy; Hematology; Minerals; Oreochromis niloticus; Pro-nutrient; Stress; Estresse; Hematologia; Minerais; Oreochromis niloticus; Saúde; Pró-nutriente